Differing commissioning arrangements may contribute to geographic variation in clinical management of digital ulcers in systemic sclerosis. Issue 3 (2020) - Reilly, Elizabeth; Alshakh, Randa; Beynon, Celia; Cates, Matthew; Das, Dhivya; Majeed, Shuja
No abstract available